(untitled) (Journal of Engineering, 2009)
A multi-cells in serial model was developed to simulate the distribution of pollutants (which are BOD5 and TDS) in Tigris river between Al-A’imma bridge and Al-Jumhuria bridge ,a reach which is about (9 km) length within Baghdad city; this includes four sewage pumping stations untreated discharged to the river. This region was divided into eleven cells of different volumes. The model was operated using the field data, which were obtained from the results of laboratory test of samples which were collected from twelve stations in the river and four sewage pumping stations located within the study region twice a month from 15/11/2005 to 30/4/2006. Verification of the simulation model was accomplished by its application to predict the substances concentrations observed. A package program of differential equation were applied to obtain the concentrations of parameters and modeling the water quality, it was concluded that the concentrations of pollutants were increased at the discharge points in the river, the concentration of BOD5 reached 140ppm at 1.4km from the beginning of the study region, 170ppm at 5km, 160ppm at 6.5km and 155ppm at 7.5km, then BOD5 became within the acceptable values in the other regions and finally it reaches the acceptable value after the last discharge point (7.8km) from the beginning of the study region, TDS was within the acceptable range except at 5km it reaches 1100ppm. sewage pumping stations shouldn’t set at high discharge rate (12 hr/day) to decrease the pollutants concentrations in Tigris river in order to keep these concentrations within the acceptable values specially at low flow of the river (250 m3/sec).By using Surfer program to show the distribution of model results (obtained from the previous program) and the field results (which were obtained from the laboratory tests) and to compute the comparison between them.